Education, Income and Happiness: Panel Evidence for the UK - Felix FitzRoy; Michael A. Nolan (Institute of Labor Economics (IZA), 2017)
Using panel data from the BHPS and its Understanding Society extension, we study life satisfaction (LS) and income over nearly two decades, for samples split by education, and age – to our knowledge for the first time. The highly educated went from lowest to highest LS, though their average income was always higher. In spite of rapid income growth up to 2008/09, the less educated showed no rise in LS, while highly educated LS rose after the crash despite declining real income. In panel LS regressions with individual fixed effects, none of the income variables was significant for the highly educated.
Keywords: I31; O47; 330; education; income; economic growth; life satisfaction; Easterlin Paradox